Effect of pre-determined maintenance repair rates on the health index state distribution and performance condition curve based on the Markov Prediction Model for sustainable transformers asset management strategies - Yahaya M.S.; Azis N.; Selva A.M.; Kadir M.Z.A.A.; Jasni J.; Hairi M.H.; Ghazali Y.Z.; Talib M.A. (MDPI, 2023)
algorithm; detection method; index method; maintenance; management practice; Markov chain; numerical method; numerical model; performance assessment; probability; repair; strategic approach